2021
DOI: 10.1007/s12043-021-02226-6
|View full text |Cite
|
Sign up to set email alerts
|

Large-amplitude dust inertial Alfvén waves in an electron-depleted dusty plasma

Abstract: The existence of the large-amplitude dust inertial Alfvén waves (DIAWs) has been presented in an electron-depleted, two-fluid dust-ion plasma. Linear analysis shows that the DIAWs travel slower than the dust Alfvén waves. DIAWs are the obliquely (with respect to the external magnetic field) propagating oscillations of dust density, having the characteristics of a solitary wave. In order to observe the nonlinear behaviour of the DIAWs, the Sagdeev pseudopotential method has been used to derive the energy balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In presence of a strong magnetic field ions get strongly magnetised in the direction of the magnetic field and moves in the direction of magnetic field only. [32]. So, equation of motion of ion in z-direction is ( )…”
Section: Y = ¶ ¶mentioning
confidence: 99%
See 1 more Smart Citation
“…In presence of a strong magnetic field ions get strongly magnetised in the direction of the magnetic field and moves in the direction of magnetic field only. [32]. So, equation of motion of ion in z-direction is ( )…”
Section: Y = ¶ ¶mentioning
confidence: 99%
“…The study of dust inertial Alfvén waves can rarely be found. Singh et al [32] considered the effect of ion inertia and discussed large amplitude dust inertial Alfvén waves in an electron-depleted dust-ion plasma. This motivates us to study the characteristics of dust inertial Alfvén solitary waves in a three-component plasma where  ,…”
Section: Introductionmentioning
confidence: 99%
“…It may be mentioned here that in deriving the linearized equations we have neglected the nonlinear term (v.∇)v in the convective derivative (∂/∂t+v.∇), valid for weak dispersion to avoid the vector nonlinearity (Sadiq et al, 2018a). Even if it is not for weak dispersion, the convective term can be neglected for the perpendicular motion (Kaur & Saini, 2016;Sadiq et al, 2018a;M. Singh et al, 2021).…”
Section: Dynamics Of Pump Kawmentioning
confidence: 99%
“…Cramer and Vladimirov [ 30 ] studied that in a dusty plasma, the wave energy propagating at oblique angles to the magnetic field in an increasing density gradient can be effectively damped by the Alfven resonance absorption process. Singh et al [ 31 ] investigated that dust inertial Alfven waves (DIAWs), the obliquely propagating oscillations of dust density with respect to the external magnetic field, have the characteristics of a solitary wave. They showed that an increase in the angle of propagation for sub‐Alfvenic DIAWs results in a decrease in amplitude while having no influence on its width and the increase in the angle of propagation leads to the decrease in both the amplitude as well as the width of the DIAWs in case of super‐Alfvenic DIAWs.…”
Section: Introductionmentioning
confidence: 99%